1998
DOI: 10.1212/wnl.51.5.1256
|View full text |Cite
|
Sign up to set email alerts
|

Is the underlying cause of epilepsy a major prognostic factor for recurrence?

Abstract: In adults, partial epilepsy is more difficult to treat than idiopathic generalized epilepsy. In patients who have partial epilepsy, the location of the epileptogenic zone does not seem to be a determining factor. Brain abnormalities--especially HS, either alone or associated with another lesion--are a major prognostic factor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

27
559
4
56

Year Published

1999
1999
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 971 publications
(646 citation statements)
references
References 23 publications
27
559
4
56
Order By: Relevance
“…Temporal lobe epilepsy (TLE) is a common form of epilepsy that is often difficult to treat (Hauser and Kurland, 1975;Hauser et al, 1991;Semah et al, 1998). Previous in vitro and in vivo studies have shown that exogenously applied CB receptor agonists, such as D 9 THC and WIN 55, 212-2 are antiepileptic in a number of animal seizure models.…”
Section: Discussionmentioning
confidence: 99%
“…Temporal lobe epilepsy (TLE) is a common form of epilepsy that is often difficult to treat (Hauser and Kurland, 1975;Hauser et al, 1991;Semah et al, 1998). Previous in vitro and in vivo studies have shown that exogenously applied CB receptor agonists, such as D 9 THC and WIN 55, 212-2 are antiepileptic in a number of animal seizure models.…”
Section: Discussionmentioning
confidence: 99%
“…Seizure severity was graded according to a modified Racine scale. 4,14 Fifteen minutes after kainate injection, the mice were injected intraperitoneally with a combination of [1-13 C]glucose (543 mg/kg) and [1,[2][3][4][5][6][7][8][9][10][11][12][13] C]acetate (504 mg/kg) and after another 15 minutes, the brains of the mice were subjected to microwave fixation at 4 kW for 1.7 seconds (model GA5013, Gerling Applied Engineering, Modesto, CA, USA). This is the most humane euthanization method instantly inactivating proteins in the brain.…”
Section: Metabolic Studiesmentioning
confidence: 99%
“…If [4,[5][6][7][8][9][10][11][12][13] C]a-ketoglutarate remains in the astrocytic TCA cycle for further metabolism via this pathway, it will, after condensation with unlabeled acetyl CoA, give rise to [3-13 C]-and [1,2-13 C]a-ketoglutarate in the subsequent turn, which may give rise to glutamate and glutamine displaying the same labeling patterns. Based on the distinct 13 C labeling in glutamine after the first and second turn of TCA cycle metabolism, a number indicative of astrocytic TCA cycle activity can be calculated by relating the amount of isotopomers generated in the second turn of TCA cycle metabolism to the amount of that generated in the first turn, i.e., ( [1,[2][3][4][5][6][7][8][9][10][11][12][13] …”
Section: Nuclear Magnetic Resonance Spectroscopymentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanisms underlying AED pharmacoresistance might be distinct from each other according to different etiologies of epilepsy, as suggested by Semah et al; 35 acquired epilepsies, such as those following stroke or due to the development of a vascular malformation or tumor, seem to be much more treatment-responsive than those associated with cortical dysgenesis, hippocampal sclerosis or dual pathologies. In the present study, subdivision of samples according to lesion etiologies was not attempted in an effort to avoid decreasing statistical power due to the small sample size.…”
Section: Discussionmentioning
confidence: 97%